The Coronation of Charles I and the Linlithgow Palace Fountain - Sally Rush (Royal Studies Journal)
The Linlithgow Palace fountain is currently understood as belonging exclusively to the reign of James V of Scotland (1512-42). This paper draws attention to the documentary and material evidence of major changes made in 1633 in preparation for Charles I’s coronation in Edinburgh and the significance of the fountain is re-examined within multiple new contexts. The changes included a classical putto holding a banderole with the text “God Save the King” and this acclamation is traced to the coronation ceremony itself as a reference to the anointing of Solomon and the Divine Right of Kings. As the creation of a monumental fountain relies upon hydraulic engineering, this paper also draws attention to the issue of water supply, and the command of nature as the magical demonstration of royal power. The masons employed in 1633 are identified by name and the fountain included with a portfolio of examples which represent the post-Reformation recovery of stone carving in Scotland under court patronage, where the introduction of a classical language of architecture symbolised the order and harmony enjoyed under Stuart rule.